Menilik Kriteria “liyan”: Mewujudkan Kerukunan Umat Beragama di Yogyakarta - Magdalena Pura Adiputra Artarini (Sekolah Tinggi Alkitab Jember, 2024)
This paper discusses the importance of religious harmony in Yogyakarta, a city with a significant number of newcomers, making it rich in diversity, one of which is religion. This diversity makes Yogyakarta also vulnerable to conflict. Through qualitative research methods with a literature study approach, the author looks at and explores the factors that influence the occurrence of intolerance. It was found that intolerance in Yogyakarta was strongly influenced by factors such as narrow-minded religious thinking, religious fanaticism, and exclusive interpretations of the concept of